Worlds Together, Worlds Apart: A History of the World from the Beginnings of Humankind to the Present - (Vol. 2: The Mongol Empire to the Present) - Authors (W. W. Norton & Company, 2008)
True to its title, this uniquely integrated text highlights the stories and themes in world history that tied cultures and regions together, and in some cases, drove them apart.